Effects of Long-Term Kerosene Spillage on Heterotrophic Microorganisms in Soil from Niger Delta, Southern Nigeria - NO Nseabasi; SP Antai (Journal of Applied Sciences and Environmental Management)
Kerosene contaminated soil was obtained from four different locations in Calabar while pristine soil served as control. Bacterial species isolated from kerosene contaminated soil samples included species of Bacillus, Pseudomonas, Micrococcus and Serratia while bacteria isolated from pristine soil samples comprised of species of Streptococcus, Salmonella, Escherichia coli, Staphylococcus aureus, Bacillus, Serratia, Micrococcus and Pseudomonas. Similar fungal species which included species of Aspergillus, Penicillium, Mucor, Rhizopus, and Fusarium were isolated from both chronic kerosene contaminated and pristine soil samples. There was no significant difference (p ≥ 0.05) in heterotrophic bacteria (HTB), fungal (HTF) and kerosene utilizing fungal counts (KUF) between chronic kerosene contaminated and pristine soil samples. However, there was significant difference (p0.05) between kerosene utilizing bacteria (KUB) between chronic kerosene contaminated and pristine samples. This revealed that long-term kerosene slippage had a selecting effect on soil bacteria as opposed to soil fungal.